An Updated Paradigm for Scale Development Incorporating Unidimensionality and Its Assessment - Gerbing, David W.; Anderson, James C. (Journal of Marketing Research, 1988)
The authors outline an updated paradigm for scale development that incorporates confirmatory factor analysis for the assessment of unidimensionality. Under this paradigm, item-total correlations and exploratory factor analysis are used to provide preliminary scales. The unidimensionality of each scale then is assessed simultaneously with confirmatory factor analysis. After unidimensional measurement has been acceptably achieved, the reliability of each scale is assessed. Additional evidence for construct validity beyond the establishment of unidimensionality then can be provided by embedding the unidimensional sets of indicators within a nomological network defined by the complete structural model.